2019
DOI: 10.1186/s13002-019-0343-y
|View full text |Cite
|
Sign up to set email alerts
|

Local perceptions and factors determining ecosystem services identification around two forest reserves in Northern Benin

Abstract: BackgroundEcosystems provide humanity with goods and services known as ecosystem services. The value of these services represents a basis for political decision-making. To be sure that these decisions are made on a valid basis, policymakers require an understanding of the biophysical processes involved. This study was carried out around two forest reserves (Alibori-Supérieur and Ouénou-Bénou) in Northern Benin. It aimed to highlight the knowledge of the surrounding communities and their perceptions about the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 46 publications
13
27
2
Order By: Relevance
“…This can be justified by the high concentration of environmental projects in the Sudano-Guinean zone than the Sudanian zone. This result corroborates those of Gouwakinnou et al (2019) who showed the critical role of environmental education sessions and the intervention of projects within the local community. For Zhang et al (2015), an environmental awareness can be explained by reforestation activities.…”
Section: Local Perception Of Ecosystem Servicessupporting
confidence: 90%
See 4 more Smart Citations
“…This can be justified by the high concentration of environmental projects in the Sudano-Guinean zone than the Sudanian zone. This result corroborates those of Gouwakinnou et al (2019) who showed the critical role of environmental education sessions and the intervention of projects within the local community. For Zhang et al (2015), an environmental awareness can be explained by reforestation activities.…”
Section: Local Perception Of Ecosystem Servicessupporting
confidence: 90%
“…This suggests that education has a positive effect on knowledge of regulating and supporting services and provisioning services. These results corroborate those of Martín-López et al (2012), Mensah et al (2017), Ahammad et al (2019), Gouwakinnou et al (2019) and Moutouama et al (2019) respectively in Bangladesh, Spain and South Africa and Benin which demonstrate that education could induce the attitude of people to support conservation policies and improve the attitude towards natural resources. Also, people age significantly influences the perception of the various ecosystem services except the supply service.…”
Section: Socio-economic Drivers Of Ecosystem Servicessupporting
confidence: 89%
See 3 more Smart Citations